Does Diversification Affect Financing Risk in Indonesian Islamic Banks? An ARDL Approach - Sururi, Sururi; Haryono, Slamet (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
Islamic banking in Indonesia faces unique challenges related to financing risks (NPF), particularly in the context of financing diversification (FDV), income diversification (IDV), and other influencing factors. This study investigates the impact of FDV, IDV, bank-specific factors, and macroeconomic variables on NPF in Indonesia’s Islamic banking sector. Using monthly data from 2016 to March 2024 and employing the ARDL approach, this study analyzes the short-term and long-term effects of these factors. The results indicate that FDV and IDV do not significantly influence NPF. Similarly, bank-specific factors such as capital (CAP), efficiency (OPE), and bank size (SIZE) are not significant determinants of NPF in Islamic banking. However, asset quality (AQ) and diversification (DIV) were found to significantly increase NPF. Among macroeconomic factors, inflation (INF) has a significant positive effect on NPF in both the short and long term, whereas the BI rate (BRT) has a significant negative effect. This research highlights the need for Islamic banks to mitigate financing risks associated with diversified products, both from PLS and non-PLS contracts, while maintaining public trust by enhancing their credibility and existence as intermediary institutions. Emphasis should be placed on optimizing product diversification strategies, improving asset quality, and monitoring macroeconomic conditions to sustain financial stability.========================================================================================================ABSTRAK - Apakah Diversifikasi Mempengaruhi Risiko Pembiayaan pada Bank Syariah di Indonesia? Suatu Pendekatan ARDL. Perbankan syariah di Indonesia menghadapi tantangan terkait risiko pembiayaan (NPF), terutama dalam konteks diversifikasi pembiayaan (FDV), diversifikasi pendapatan (IDV), dan faktor lainnya. Penelitian ini menyelidiki dampak FDV, IDV, faktor spesifik bank, dan variabel makroekonomi terhadap NPF di sektor perbankan syariah Indonesia. Menggunakan data bulanan dari tahun 2016 hingga Maret 2024, penelitian ini menganalisis efek jangka pendek dan panjang dari faktor-faktor tersebut dengan pendekatan ARDL. Hasil penelitian menunjukkan bahwa FDV dan IDV tidak berpengaruh signifikan terhadap NPF. Begitu juga dengan faktor spesifik bank seperti modal (CAP), efisiensi (OPE), dan ukuran bank (SIZE) tidak menjadi determinan signifikan. Akan tetapi, kualitas aset (AQ) dan diversifikasi (DIV) menunjukkan pengaruh yang signifikan terhadap peningkatan NPF pada bank syariah. Diantara sekian faktor makroekonomi, inflasi (INF) memiliki pengaruh positif signifikan terhadap NPF dalam jangka pendek dan panjang, sedangkan BI rate (BRT) memiliki pengaruh negatif signifikan. Penelitian ini menyoroti pentingnya bagi bank syariah mengurangi risiko pembiayaan yang muncul dari produk diversifikasi, baik dari kontrak PLS maupun non-PLS, sambil mempertahankan kepercayaan publik dengan meningkatkan kredibilitas dan eksistensinya sebagai lembaga intermediasi. Perhatian harus difokuskan pada optimalisasi strategi diversifikasi produk, peningkatan kualitas aset, dan pemantauan kondisi makroekonomi untuk menjaga stabilitas keuangan.